Migraine Disgraceful Event of Peaceful Life : A Review (Homoeopathy for All, 2021)
Migraine is the typical variety of headache and is an actual cause of severe pain in the head. Such pain is typically paroxysmal, but it requires being to be relieved. Homoeopathic management is significant and is expected to be more effective when the physician has a comprehensive knowledge of the clinical presentation of the condition and triggering factors along with relevant information related to migraine available in the homoeopathic literature. This article tries to present such material with the idea of helping the homoeopathic physician to manage the condition even better and along with improving quality of life by minimizing suffering. This article also discusses the homoeopathic approach towards migraine and also highlights the limitation of conventional treatment by modern medicine.
Keywords: Migraine; Sick Headache; American Sick Headache; Homoeopathy